Recommendations for diagnosis and treatment of patients with lung cancer - Martina Vrankar; Nina Boc; Izidor Kern; Aleš Rozman; Karmen Stanič; Tomaž Štupnik; Mojca Unk; Maja Ebert Moltara; Vesna Zadnik; Katja Adamič; Jernej Benedik; Marko Bitenc; et al. (Onkologija, 2023)
In 2019, the Recommendations for the management of patients with lung cancer were published bringing much-needed standardisation of diagnosis and treatment to improve survival of patients with lung cancer. Three years after the original Recommendations were published, the update of the Recommendations brings the most innovations in the chapter on systemic treatment of patients with lung cancer. This reflects the remarkable progress made in the field of understanding the oncogenesis and biology of lung cancer and thus the development of new drugs. The burden of lung cancer remains high, as lung cancer is still the most common cause of cancer related death in our country and worldwide. Lung cancer is responsible for one of five cancer-related deaths. Almost one third of patients with lung cancer do not receive any oncological treatment, either because of poor performance status, comorbidities or the extent of the disease. Half of the patients have metastatic disease at diagnosis, resulting in only small improvements in survival despite advances in the treatment of lung cancer patients. These data remind us that if we are to make major shifts in the management of lung cancer patients, we will need to take different approaches. The most promising seems to be the detection of early stages of lung cancer which offers the best treatment results. The Recommendations written here are guidelines for the management of patients with lung cancer. Only with comprehensive multidisciplinary treatment approach, the best outcome from the prognostically unfavourable disease can be offered.